Witchcraft or Otherness - Tomaž Onič (Acta Neophilologica, 2023)
Tituba, a supporting character in Arthur Miller’s 1953 play The Crucible, can be associated with the concept of otherness in several respects. For one, she is not free like the rest of the population of Salem, Massachusetts, where the play is set, but was brought to the community from the island of Barbados by Reverend Parris as an enslaved woman. Being of Caribbean origin, she is also not an English Protestant like the rest of the village, and despite having accepted her master’s church, as was common for the enslaved throughout the British colonial period, Protestantism is not her first religion. Finally, the two most evident and immediately perceivable characteristics placing her in the category of the Other are her skin colour and her language, which also seem to be the main reasons that she was the first person to be accused of witchcraft in Salem. This paper focuses on Tituba’s speech, particularly from the point of view of the possibilities as well as difficulties of translating her utterances into Slovene. The contrastive analysis includes Miller’s original play, its two Slovene translations, Lov na čarovnice, the published one (1964) and the unpublished theatre translation (1997/2019), as well as a brief insight into two theatre productions of the play at the Maribor National Theatre.